The sea of monsters - Riordan, Rick. (New York : Miramax Books/Hyperion Books for Children, 2006)
Demi-god Percy Jackson and his friends must journey into the Sea of Monsters to save their camp. But first Percy will discover a secret that makes him wonder whether being claimed as Poseidon's son is an honor or a cruel joke.
740
Accelerated Reader AR
Keywords: Mythology, Greek -- Juvenile fiction; Camps -- Juvenile fiction; Friendship -- Juvenile fiction; Fathers and sons -- Juvenile fiction; Poseidon (Greek deity) -- Juvenile fiction; Hades (Greek deity) -- Juvenile fiction; Zeus (Greek deity) -- Juvenile fiction; Fantasy fiction